Intrusion Detection Systems in Wireless Sensor Networks: A Review. (19th May 2013) - Alrajeh, Nabil Ali; Khan, S.; Shams, Bilal
Abstract : Wireless Sensor Networks (WSNs) consist of sensor nodes deployed in a manner to collect information about surrounding environment. Their distributed nature, multihop data forwarding, and open wireless medium are the factors that make WSNs highly vulnerable to security attacks at various levels. Intrusion Detection Systems (IDSs) can play an important role in detecting and preventing security attacks. This paper presents current Intrusion Detection Systems and some open research problems related to WSN security.